GLAM-Wiki: Wikipedia as an opportunity for cultural institutions - Saorín, Tomás (Anuario ThinkEPI, 2013)
This article explains how libraries, archives, museums and other cultural centres are involved in the Wikimedia Foundation's free knowledge projects, such as Wikipedia and Wikimedia Commons. It also describes activities that strengthen openness in topics of interest to cultural institutions and generate enthusiasm through article edit-a-thons and other participatory initiatives.
Keywords: Wikipedia; Free content; Cultural heritage.